Prosedur Penyaluran Dana Desa Di Provinsi Jawa Barat (Studi Pada BPKAD Provinsi Jawa Barat) - Intan Sakina; Asep Suherman (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
The objectives of the study were 1) to find out the procedures for channeling village funds in West Java Province, and 2) to find out the inhibiting factors for the procedure for channeling village funds in West Java Province. This research method is qualitative. Data collection techniques used were using interviews, observation, and documentation. The results of this study show that the procedure for channeling village funds in West Java Province is still experiencing problems. The factors that hinder the procedure of channeling village funds in West Java Province are: incompleteness of disbursement requirements documents, invalidation of disbursement requirements documents, erroneous data in the disbursement request letter and its attachments from the West Java Province DPMD, lack of understanding of the implementers of verifications in the West Java Province DPMD keep submitting the retirement documents that are still incomplete and correct, the completion of the document improvement is very long.